A cross-sectional study on the relationship between dietary fiber and endometriosis risk based on NHANES 1999–2006 - Zheng, Ya-Fang; Guo, Yu-Miao; Song, Chu-Jun; Liu, Gui-Chao; Chen, Shi-Yi; Guo, Xu-Guang; Lin, Li-Hong (Scientific reports, 2024)
Endometriosis is a chronic inflammatory disease and an estrogen-dependent disease, so dietary factors that can modulate estrogen activity may be clinically important. Dietary fiber, widely distributed in vegetables and fruits, is closely associated with a plant-based diet. Therefore, this study aims to analyze and explore the relationship between dietary fiber intake and the risk of endometriosis providing insights for future clinical significance and treatment approaches. This cross-sectional study obtained data from the National Health and Nutrition Examination Survey (NHANES) 1999–2006 for women aged 20–54 years. A total of 2840 subjects were finally included for analysis, 2599 (91.51%) in the non-endometriosis group and 241 (8.49%) in the endometriosis group. The study used dietary fibre intake as exposure variable and endometriosis risk as outcome variable. Through the use of multiple regression modelling, subgroup analyses, smoothed curve fitting, and threshold effect tests, we uncovered a significant link between exposure and outcome. In Model 2 (Multiple regression equation model after adjusting all confounding variables), after adjusting for confounders, dietary fiber intake was negatively associated with the likelihood of developing endometriosis(OR = 0.588, 95% CI = 0.360–0.959, p = 0.041). In subgroup analyses stratified by age, race, BMI, educational level, hypertension, diabetes,and hyperlipidemia, significant interactions were visualised from smoothed fitted curves. In the cross-sectional study, a connection was observed between a higher intake of dietary fiber and a decreased risk of endometriosis.